Paguyuban Sumarah and Interrituality: An Enquiry to The Practice of Interreligious Ritual Participation in Sujud Sumarah - Maulana, Abdullah Muslich Rizal; Muttaqin, Muttaqin; Fitriyani, Alif Nur (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
Paguyuban Sumarah is one well-known aliran kepercayaan in Indonesia existed since the 1930s. The group practised Sujud Sumarah as the most essential ritual attended by the whole member of organizations from multiple religious backgrounds and identities, gathering them in a venue of interreligious ritual participation. This paper will discuss the aspect of interrituality in Sujud Sumarah, considering it is practised by multi-religious believers through the discourse-analysis method following the framework of interrituality offered by Moyaert, an interreligious scholar from Vrije Universiteit Amsterdam. This research concludes that it is acceptable to define the implementation of Sujud Sumarah as an interreligious ritual participation, yet it could not explicitly be categorized as ‘inner-facing’ or ‘outer-facing’ interrituality as it was classified by Moyaert. This paper also demonstrated, in general, the fundamental system of belief of Sumarah was derived from syncretism and transcendent unity of religions, leading the discussion to be possibly elaborated further in the study of interreligious relations.